Perancangan Mesin Pencacah Tandan Kosong Kelapa Sawit - Nasirly, Riri; Kurnia, Anggi Rada; Laila, Widya; Arsi, Fadli; Rahmad, Nuraini; Larasati, Tengku Indira (Kohesi: Jurnal Sains dan Teknologi, 2024)
Indonesia is one of the world's largest suppliers of palm oil needs. Increasing the area of oil palm plantations followed by CPO production does not always have a positive impact, especially related to waste. Palm Oil Empty Bunches (EFB) is one of the largest wastes generated from the palm oil processing industry, where the amount reaches 21-23% of fresh fruit bunches. So far, the use of empty oil palm bunch waste is very limited, namely landfilled (open dumping) and burned. One of the uses of waste from TKKS is as fertilizer The initial stage to be able to make EFB compost is by enumerating EFB to accelerate decomposition. So that shredding technology is needed in the process of making EFB compost. Most of the Palm Oil Industry has used large capacity shredding machines. However, for small farmers to have machines with these standards cannot be done so the purpose of this study is to design a small-scale EFB counter. The speed for the enumeration process with 300 Rpm takes 6.3 minutes, and 500 Rpm with a time of 5.3 minutes.